Infection prevention and control in health care settings during COVID-19 pandemic - Fatema, Kaniz; Barai, Lovely (BIRDEM Medical Journal, 2020)
Infection prevention and control (IPC) practices are of critical importance in protecting the frontline healthcare providers in the ongoing Coronavirus disease 2019 (COVID-19) pandemic and keep the healthcare services functioning. Healthcare facilities should apply strict IPC measures to minimize the risk of transmission of COVID-19 to their staff and other patients. The backbones of IPC in healthcare facilities are administrative measures, physical distancing, hand hygiene and the appropriate use of personal protective equipment. All healthcare workers working in any type of healthcare settings must have proper knowledge of IPC. Rational, correct and consistent use of personal protective equipment according to level of exposure to patients decreases the transmission of pathogens and protects the frontline fighters. Cleaning and disinfection procedures of environmental surfaces, medical devices and equipments, laundry etc must be done correctly and consistently. Administrative authority should provide logistic support, arrange training for health care personnel and monitor their compliance to IPC practices. As there is still no definite treatment of this disease, comprehensive IPC programmes are the only hope to control this pandemic. Birdem Med J 2020; 10, COVID Supplement: 81-92